The Argentinean attempts to prove the Theory of General Relativity: the total solar eclipses of 1912, 1914 and 1919 - Paolantonio, Santiago (2019)
Fil: Paolantonio, Santiago. Observatorio Astronómico de Córdoba - Museo Astronómico; Argentina